New Trends in Nanoarchitectured SERS Substrates: Nanospaces, 2D Materials, and Organic Heterostructures. Issue 25 (15th May 2022) - Guselnikova, Olga; Lim, Hyunsoo; Kim, Hyun‐Jong; Kim, Sung Hyun; Gorbunova, Alina; Eguchi, Miharu; Postnikov, Pavel; Nakanishi, Takuya; Asahi, Toru; Na, Jongbeom; Yamauchi, Yusuke
Abstract: This article reviews recent fabrication methods for surface‐enhanced Raman spectroscopy (SERS) substrates with a focus on advanced nanoarchitecture based on noble metals with special nanospaces (round tips, gaps, and porous spaces), nanolayered 2D materials, including hybridization with metallic nanostructures (NSs), and the contemporary repertoire of nanoarchitecturing with organic molecules. The use of SERS for multidisciplinary applications has been extensively investigated because the considerably enhanced signal intensity enables the detection of a very small number of molecules with molecular fingerprints. Nanoarchitecture strategies for the design of new NSs play a vital role in developing SERS substrates. In this review, recent achievements with respect to the special morphology of metallic NSs are discussed, and future directions are outlined for the development of available NSs with reproducible preparation and well‐controlled nanoarchitecture. Nanolayered 2D materials are proposed for SERS applications as an alternative to the noble metals. The modern solutions to existing limitations for their applications are described together with the state‐of‐the‐art in bio/environmental SERS sensing using 2D materials‐based composites. To complement the existing toolbox of plasmonic inorganic NSs, hybridization with organic molecules is proposed to improve the stability of NSs and selectivity of SERS sensing by hybridizing with small or large organic molecules. Abstract : A summary of advances in developing surface‐enhanced Raman spectroscopy (SERS)‐active substrates via fabrication methods of nanostructured metals and 2D materials is provided. Approaches for controlling metal tips/gaps/pores including advantages and disadvantages are discussed. Moreover, recent advances and challenges of novel 2D‐layered SERS‐active substrates are presented. Functionalization strategies for SERS surfaces include use of small or large molecules to complement the preparation procedures.